(untitled) (Research, Society and Development, 2021)
The aim of this study was to review the information provided by the Terms of Reference related to the activities of the Food and Nutrition Units in hospitals. This was an exploratory study, based on the TRs of eight state-run hospitals in Bahia that outsource their Food Services. An instrument was drafted with 32 assertions organized into three categories: Menu Planning, Menu Execution, and Hygiene and Sanitary Control. Whether or not they were explicit was also considered. Menu Planning had 57.5% of items included in the Terms of Reference, while Menu Execution and Hygiene and Sanitary Control reached 66.7% and 80.7%, respectively. Only the first item did not have the same percentage in relation to the topics that were explicitly stated. The lack of essential information for the execution of the activities of a Food Services in a hospital was verified, including: the person responsible for elaborating the menus, staff sizes, hygienization of the water tanks, and training of workers. The conclusion is that more specific TRs are needed.